Pengaruh Atmosfer Cafe, Kualitas Produk dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Station Coffee Premium Kota Lhokseumawe - Moulana Alfajar Putra; Adnan Adnan; Siti Maimunah (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2021)
The purpose of this study was to examine the effect of cafe atmosphere, product quality and service quality on customer satisfaction at station coffe premium in lhokseumawe city. The population in this study was all customers in station coffe premium in lhokseumawe city. While the sample is 100 respondents. The sampling technique is accidental sampling. The type of data used in this study is primary data in the form of cross selection data which is obtained using a questionnaire. The data analysis method in this research is the multiple linear regression analysis method for panel data. The results of the study found that partially the cafe atmosphere has a significant effect on customer satisfaction partially the product quality has an effect on customer satisfaction. while partially service quality has an effect on customer satisfaction. and cafe atmosphere, product quality and service quality simultaneously influence customer satisfaction